Malignant transformation of primary ameloblastoma of skull: case report and review of current literature - Xu, Haitong; Tan, Jialiang; Fu, Dongxiang (Frontiers in Oncology, 2024)
Background: Since 1964, there has been a scarcity of reported cases of primary ameloblastoma (AM) or ameloblastic carcinoma (AMCa) of the skull. The clinical presentation and distinctive features of this uncommon condition at specific anatomical sites remain unclear.We report a case of malignant transformation of a primary AM of the skull situated in the frontal-temporal-parietal region and highlight its similarities to other cases reported in the literature. Clinical presentation: A 53-year-old female patient presented with a 20-day history of headaches and bilateral lower limb weakness for 10 days. Physical examination revealed slow and unsteady gait. An occupying lesion was observed in the right frontal-temporal-parietal region of the skull on the Cranial imaging. A right cranial bone tumor margin expansion resection was performed. The patient’s motor functions recovered normally after surgery. Postoperative imaging examinations showed tumor resection . Follow-up imaging examinations showed tumor recurrence. The patient underwent resection of the recurrent tumor. Postoperative pathological analysis revealed malignant transformation of the AM.Follow-up imaging examinations showed tumor recurrence again. The patient was admitted for stereotactic radiotherapy. Follow-up imaging examinations demonstrated no evidence of tumor recurrence and subsequent chest CT revealed no signs of metastasis. Conclusion: Primary AM or AMCa of the skull is increasingly being described in the literature, but detailed reports on the malignant transformation of primary AM of the skull are lacking. The pathogenesis of this condition remains unclear. Aggressive treatment and close follow-up may be crucial for preventing disease recurrence and malignant transformation.